THE INFLUENCE OF MEDIA USE FLANNEL BOOK IMAGINATION AGAINST THE READING SKILLS OF UNDERSTANDING CHILD MENTAL RETARDATION LIGHTWEIGHT CLASS VIII IN SKH MADINA CITY OF SERANG - Ainun Marlia; Dr. Hj. Isti Rusdiyani, M.Pd; Toni Yudha Pratama, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
AbstractThe purpose of this research is to know the media use flannel book imagination against the ability of reading comprehension in children mental retardation in SKH Madina Serang. The methods used in the study is a method of experiments with one-design research group pre test post test. Research data obtained from either a hasl multiple choice question test conducted on initial conditions before being given treatment, when given a treatments, and after being given the treatment. Processing of research data using statistical calculations nonparametris through the wilcoxon test. Place research at the SKh Madina City Attack with the total sample as many as three students mental retardation. The research showed the media flannel book imagination can enhance the ability of reading comprehension in students ' mental retardation. The difference between the two can prove that there is a growing understanding of the reading ability in students mental retardation in SKh Madina Serang. This is evidenced by the pre-order test score view seen from the score that indicates the lowest score in the can is 3 students (20%) and the highest score of the students is 9 (60%) of a total of 15 grains of matter and score the lowest post-test the students is 9 (60%) and the highest score of the students is 12 (80%). Of a total of 15 item reserved then it can be inferred media flannel book imagination can improve the reading comprehension of students ' mental retardation.